(untitled) (International Journal of Engineering and Computer Science, 2018)
In modern life we have to face many problems because of traffic congestion. It is said that the high volume of vehicles, the inadequate infrastructure and the irrational distribution of the development are main reasons for increasing traffic jam. The major reason for traffic congestion is the high number of vehicle which was caused by the increase in population and the development of economy. Traffic congestion is a condition that occurs as use increases, and is characterized by slower speeds, longer trip times, and increased vehicular queuing. Here in my proposed work I am depending on 8 different roads that meet at a single junction. In that i will consider pedestrian, vehicles, and ambulance and red light violation detection persons too. The use of RFID and GPS will help to make the lane clear for ambulance. Using the RFID we can detect the red light violators and we can assign fine to them. Lastlly for pedestrian I am providing one subway and one overbridged.